The topological transformation of Freud's theory (Karnac Books, 2016)
In this book the author presents his reading of psychoanalysis in the spirit of its founder Sigmund Freud, and explores the transformations of Freud's work by his followers. The author notes that some of these followers trimmed it down even to exclude the death drive, which was one of Freud's fundamental principles. Freud's theory has also been transformed by Lacan, who, in the mid-1950s embarked on a lifelong enterprise to recast it in a fruitful debate with the sciences and the humanities. Such a transformation brought by Lacan was (somewhat paradoxically) necessary to show the importance of Freud's findings for the understanding of subjectivity.